A Morphological Study of Traditional Shophouse in China and Southeast Asia. (28th April 2015) - Han, Wang; Beisi, Jia
Abstract: From the rise of Maritime Silk Road to nowadays, with the globalizational impacts from economic, cultural, political, technological and other aspects, the evolutionary process of urban housing in China and Southeast Asia has been presenting a diversified and hybrid tendency. While at the same time, it is difficult to recognize the commonness and individuality between local and foreign culture during the process of cultural fusion. To awaken regional identities and assimilate foreign advanced civilizations, this paper traces to the ancient time - Maritime Silk Road. Based on the influence of the "Road", through morphology and culturology analysis, traditional shophouses in different Chinese and Southeast Asian areas are studied. Focusing on three different levels including "urban", "street" and "building", some basic "prototypes" are summed up and analyzed in macro-perspective. Furthermore, three typical types of shophouse in different commercial cities are selected to do comparative study. All of the cities have been profoundly influenced by Maritime Silk Road in the past time, including Quanzhou, Guangzhou, and Malacca. By describing the spatial forms and tectonic modes of these cases, the regional, epochal and cultural characters expressed by shophouse are expounded. Meanwhile the cultural exchange and interaction on Maritime Silk Road reflected by traditional shophouse is demonstrated in this paper.